Randomised clinical trial: Lactobacillus GG modulates gut microbiome, metabolome and endotoxemia in patients with cirrhosis. Issue 10 (16th March 2014) - Bajaj, J. S.; Heuman, D. M.; Hylemon, P. B.; Sanyal, A. J.; Puri, P.; Sterling, R. K.; Luketic, V.; Stravitz, R. T.; Siddiqui, M. S.; Fuchs, M.; Thacker, L. R.; Wade, J. B.; et al.
Summary Background Safety of individual probiotic strains approved under Investigational New Drug (IND) policies in cirrhosis with minimal hepatic encephalopathy (MHE) is not clear. Aim The primary aim of this phase I study was to evaluate the safety, tolerability of probiotic Lactobacillus GG (LGG) compared to placebo, while secondary ones were to explore its mechanism of action using cognitive, microbiome, metabolome and endotoxin analysis in MHE patients. Methods Cirrhotic patients with MHE patients were randomised 1:1 into LGG or placebo BID after being prescribed a standard diet and multi‐vitamin regimen and were followed up for 8 weeks. Serum, urine and stool samples were collected at baseline and study end. Safety was assessed at Weeks 4 and 8. Endotoxin and systemic inflammation, microbiome using multi‐tagged pyrosequencing, serum/urine metabolome were analysed between groups using correlation networks. Results Thirty MHE patients (14 LGG and 16 placebo) completed the study without any differences in serious adverse events. However, self‐limited diarrhoea was more frequent in LGG patients. A standard diet was maintained and LGG batches were comparable throughout. Only in the LGG‐randomised group, endotoxemia and TNF‐α decreased, microbiome changed (reduced Enterobacteriaceae and increased Clostridiales Incertae Sedis XIV and Lachnospiraceae relative abundance) with changes in metabolite/microbiome correlations pertaining to amino acid, vitamin and secondary BA metabolism. No change in cognition was found. Conclusions In this phase I study, Lactobacillus GG is safe and well‐tolerated in cirrhosis and is associated with a reduction in endotoxemia and dysbiosis.